Pengaruh Pemberian Urin Kelinci Terhadap Serangan Turnip Mosaic Virus (TuMV) Pada Tanaman Kailan (Brassica oleraceae var. alboglabra) yang Dibudidayakan Secara Organik - Fery Abdul Choliq; Mintarto Martosudiro; Qurrota Ayuni Apriliana; Istiqomah Istiqomah (AGRORADIX : Jurnal Ilmu Pertanian, 2019)
Kai Lan has a high potential for being developed in Indonesia. The cultivation system that can produce high quality product that is organically cultivated of kai Lan. Organic plant cultivation require intensive maintenance. The disease that often attacks kailan plants is a mosaic disease caused by Turnip Mosaic Virus (TuMV). The purpose of this research was to find out the effect of giving rabbit urine against TuMV attack of kai Lan and to know the effect on growth and production of kai lan. Research conducted in the Organic Community Brenjonk Mojokerto regency, East Java. The research was conducted from February to April 2016. The Research used randomized block design (RBD) with six treatments and each treatment was repeated four times. The observation variable are include incubation period and symptoms of the disease, the intensity attack of disease, plant height, plant weigh, length, roots, and broad leaf of plants. The result of observation showed that rabbit urine with a consentrate 8ml/L up to 32ml/L applied as much as 8 times, can extend the incubation period and can’t decrease the intensity of TuMV attack. Rabbit urine with a consentrate 8ml/L up to 32ml/L also applied as much as 8 times on the plant can increase the growth and production of kai lan include fresh weight of plant, plant height, plant root length and leaf area of plant.